2013
DOI: 10.1136/ejhpharm-2013-000276.335
|View full text |Cite
|
Sign up to set email alerts
|

DGI-069 The Importance of Clinical Pharmacist Counselling in Improving Patient Medication Adherence

Abstract: Background Adherence is a key factor in achieving good clinical outcomes in patients undergoing long-term treatment. Meeting with patients is fundamental in educating them on correct drug use, and recommending dietary and lifestyle changes. Purpose To assess the clinical pharmacist (CP) counselling programme, up to the discharge and outpatient visits, to improve medicines adherence, reduce adverse drug events, and encourage positive behaviour. Materials and Methods CP counselling was addressed to adult abdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This highlights the fact that patient counseling can improve medication adherence as suggested by Carollo et al [9].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This highlights the fact that patient counseling can improve medication adherence as suggested by Carollo et al [9].…”
Section: Discussionmentioning
confidence: 69%
“…Proper education regarding all the abovementioned aspects of medication plays a significant role in improving medication adherence, which in turn helps in achieving optimal glycemic control [9]. Standard patient counseling may be less effective in this, so combination of multiple patient counseling techniques like to teach-back method, use of patient information leaflets and video results in a better improvement in adherence [10].…”
Section: Introductionmentioning
confidence: 99%
“…4 So, providing pharmaceutical care through patient counseling would be supportive in the healthcare system and also plays an immense role in reducing nonadherence among the patients. 7 The study observed that some of the demographic, disease and therapy related characteristics of the patient population also affect adherence in various ways. 4 Advancing age affects adherence by increase in chance of forgetfulness, lack of assistance and polypharmacy which is supported by a study conducted in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Thus, today’s pharmacist will evolve to conduct research in pharmacovigilance, prescription patterns, antibiotic use and misuse, drug adherence, drug interaction, nuclear medicine, and specialized areas of treatment. [10]…”
Section: Discussionmentioning
confidence: 99%